Original papersClinical outcomes and effectiveness of renal artery stenting in patients with critical atherosclerotic renal artery stenosis: does it improve blood pressure control and renal function assessed by estimated glomerular filtration rate? - Yildiz, Mustafa; Aykan, Ahmet ÇağrI; Karakoyun, Suleyman; Gokdeniz, Tayyar; Karabay, Can Y.; Akin, Ibrahim; Gul, Cetin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : Atherosclerotic renal artery stenosis (ARAS) is associated with uncontrolled hypertension and chronic renal failure. Aim: To evaluate the influence of gender and presence of chronic renal failure on the outcomes of percutaneous transluminal renal artery stenting (PTRAS) due to atherosclerosis. Material and methods: A total of 28 ARAS patients underwent PTRAS and 36 stents were placed. Basal characteristics, laboratory data and blood pressure of patients were recorded. The differences between genders and improvement/deterioration of renal functions and blood pressure were analyzed. The predictors of outcomes were determined. Results : Baseline characteristics were similar between men and women. Significant improvement of systolic and diastolic blood pressure control was achieved after PTRAS (153.04 ±17.07 mm Hg vs. 124.75 ±11.40 mm Hg, p = 0.001 and 92.50 ±10.76 mm Hg vs. 77.54 ±8.23 mm Hg, p < 0.001, respectively). Although mean estimated glomerular filtration rate (eGFR) and creatinine levels did not significantly improve at the 6-month follow-up visit compared to baseline values, of the 28 patients 13 (46.4%) patients had improvement of renal functions. Conclusions : Our results suggest that PTRAS is a safe procedure and may offer blood pressure control but beneficial effects of PTRAS on renal function may be anticipated in a selected group of patients, especially those with a low eGFR.